2014
DOI: 10.1093/ejcts/ezu229
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastroepiploic arterial grafts to right coronary artery using transit-time flow measurement

Abstract: Previously reported cut-off values for intraoperative TTFM parameters could not be adapted for the early patency of GEA grafts to the RCA. However, the smoothness of the graft-flow curve may be a reliable predictor of postoperative graft patency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In CABG surgery, early graft failure is not infrequent, with an occurrence rate of 5% to 20% . With the introduction of TTFM, the cardiac surgeon can now not only document the patency of their anastomoses at the end of the operation but can also better assess the functional capacity of the grafts they perform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In CABG surgery, early graft failure is not infrequent, with an occurrence rate of 5% to 20% . With the introduction of TTFM, the cardiac surgeon can now not only document the patency of their anastomoses at the end of the operation but can also better assess the functional capacity of the grafts they perform.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review of published TTFM studies, Niclauss et al concluded that the mean graft flow positively predicts long‐term patency (minimum threshold of 20 mL/min for IMA grafts and 30‐40 mL/min for vein grafts) . Coronary artery bypass graft failure has been associated with the following: high fractional flow reserve (FFR) (which was also associated with high mean PI, probably due to competitive, antegrade flow from the native coronary artery); TTFM measurements in the early diastolic phase; smoothness of the graft‐flow curve for arterial grafts; and high PI and high systolic reverse flow . Published work from our group has shown that differences of TTFM parameters between left‐ and right‐sided vein grafts were small and unlikely to be of clinical relevance …”
Section: Discussionmentioning
confidence: 99%
“…Although a statistically significant correlation between TTFM and flow at follow-up has been debated, most studies agree on PI being directly and independently related to increased risk of graft failure or adverse inhospital cardiac events [5,8,14,16,26], albeit with a few exceptions [20,25,31].…”
Section: Cutoff Value For Pimentioning
confidence: 99%
“…Contrary to ITAs and SV grafts, Lehnert et al 21 did not find any correlation between MGF and RA graft failure, but general conclusions are limited due to the small number of the studies. Similarly, Uehara et al 25 found no significant differences in MGF values of occluded versus patent RGEA grafts to the RCAs. They suggested that the MGFs of patent RGEA grafts are relatively lower than the value obtained with ITA or SV grafts, because RGEA is a visceral artery and the fourth branch of the aorta.…”
Section: Mgf and Graft Conduitsmentioning
confidence: 89%